Proteção ambiental do trabalhador rural na agricultura canavieira - Franco, Dulcely Silva (2018)
This study pursues to comprehend the rural labor environment in sugarcane agriculture and its main risks to the health, life and well-being of the rural workers, as well as to verify if the human and fundamental rights as for the labor-environmental balance and the health of these rural workers, notably the sugarcane cutters, would be being violated. From this, it intends to describe principles and rules applicable to the protection of these rights and discuss its efficiency and effectiveness from the analysis of the acting of public and private social actors involved. The technical procedures to this investigation were bibliographic and documental research, interviews, observation and theoretical-normative investigation.